Evaluation of the Thyroid Incidentelomas of the Patients Detected on F-18 FDG PET/CT - Simsek, F. S.; Koc, Z. P.; Balci, T. A.; Kuslu, D.; Narin, Y.; Donder, E.; Ozercan, I. H. (Springer, 2016)
[Abstract Not Available]
Annual Congress of the European-Association-of-Nuclear-Medicine -- OCT 15-19, 2016 -- Barcelona, SPAIN
Keywords: thyroid; insidenteloma; F-18; FDG; lymph node